Determinação instantânea da relação água-cimento e da resistência à compressão do concreto no estado fresco através do método da resistividade elétrica - Braun, Carlos Eduardo (Universidade do Vale do Rio dos Sinos, 2015)
During construction of concrete elements in the building site, quality control proceedings are adopted in order to verify if the concrete reaches its design specifications, which also avoids failures during the subsequent stages of the construction. Test methods used for the determination of the water-cement (w/c) ratio have received increased attention, due to the importance of this ratio for the concrete resistance and durability, and also because there isn’t any practical and sufficiently precise method available at the moment, which could be used for determining water-cement ration after mixing. Studies about the electrical resistivity method have shown a strong relationship between the measured resistivity values and water-cement ratio, for the fresh concrete, making this method an interesting alternative for determining w/c ratio. This study presents an analysis of the electrical resistivity method, applied to determine the water-cement ratio of several fresh concrete mixtures made with different types of Brazilian cements, in addition to estimates of compressive strength values of the hardened concretes. Concrete mixtures were made out of six cement types (CPV-ARI, CPIV-32, CPIII-40, CPII-Z-32, CPII-F-32 and CPII-E-40), dosed by the IPT/EPUSP method, and four water-cement ratios (0.35, 0.45, 0.55 and 0.65). Tests were performed using an improved probe, developed in this study, based in one prototype developed previously. Results shown a strong relationship between the electrical resistivity of fresh concrete and its water-cement ratio, with average estimated values within ±0,02 of the actual water-cement ratio values for the mixtures tested. The average error for the w/c ratio estimated values, considering all of the cements tested, was between 2,25% and 9,38%. The compressive strength estimates reached coefficients of determination between 85,7% and 95,2%, showing that it is possible to estimate both w/c ratio and compressive strength of concrete while still in the fresh state with the electrical resistivity method presented here.
Keywords: Resistividade elétrica; Relação água-cimento; Concreto no estado fresco; Controle de qualidade do concreto; Electrical resistivity; Water-cement ratio; Fresh concrete; Concrete quality-control; ACCNPQ::Engenharias::Engenharia Civil